Student Literacy and Literacy Skills in Higher Education: A Bibliometric Review - Asep Purwo Yudi Utomo; Dwi Yuwono Puji Sugiharto; Rossi Galih Kesuma; Diyamon Prasandha (International Journal of Pedagogy and Teacher Education, 2024)
Student literacy and literacy skills are crucial in developing critical thinking, analytical abilities, and overall academic success in higher education. This study provides an initial overview of research developments on these topics through a bibliometric analysis of studies published between 2004 and 2023. Data were collected from the Scopus database, identifying 675 relevant publications, and analyzed using tools such as Scopus, Mendeley, and VOSViewer to explore research trends, dominant keywords, and collaboration networks in this field. The findings reveal that studies on student literacy have steadily increased over the past two decades, with the United States and Indonesia as leading contributors. Key themes frequently emerging in these studies include literacy, students, writing, reading, and teaching. Despite this growing interest, research specifically linking literacy and student literacy skills in higher education remains limited, with most studies focusing on general literacy aspects. These insights highlight the need for further exploration, particularly in developing students' critical literacy skills in higher education contexts. This study aims to map the landscape of student literacy research, provide insights into researcher contributions, and identify research gaps for future studies. Ultimately, these findings can guide future research and policy development to enhance literacy skills critical for academic success and professional readiness.